Stongde revisited: land-use change in Central Zangskar - Dame, Juliane; Mankelow, J. Seb (ERDKUNDE, 2010)
Modifications of the mostly subsistence-based economy and a general trend towards livelihood diversification are characteristic dynamics in high mountain regions. Using a case study from the Himalayan village of Stongde in Zangskar (Northern India), current trends in land utilization, work patterns and livelihood strategies are presented and discussed. The assessment of persistence and change of land-use patterns and strategies over a period of almost three decades is based on a comparative analysis of Henry Osmaston’s studies in the case study village in 1980 and recent field research by the authors. The study shows a high persistence of field structures fostered by a set of environmental, political and social factors. At the same time, the survey illustrates a diversification of the cropping pattern and recent agricultural trends. High mountain livelihoods are modified by a number of internal and external factors, including new agricultural practices, rural development initiatives, food subsidies and off-farm income.